Kings of L.A. [videorecording (DVD)] - Dean, Francois (2023)
A young man reaches a critical point in his lifeas he struggles to navigate the changing gentrification of his neighborhood. Pressured by gangs, the temptations of easy money and the culture shifts around him in South Central as he tries to figure out how to survive when everyone wants a piece of him and his neighborhood.